Experimental evaluation of different influencing parameters on cutting transport performance (CTP) in deviated wells - Iqbal, Sayed Muhammad; Hussain, Altaf; Ali, Nafees; Hussain, Wakeel; Hussain, Hadi; Hussain, Sadam; Shah, Syed Yasir Ali; Nyakilla, Edwin E. (Geosystems and geoenvironment, 2023)
•CTP in deviated wells is affected by influencing parameters e.g. viscosity, annular velocity, and angle.•At all angles, CTP has enhanced up to 10 % by increasing viscosity while keeping velocity constant.•An increasing additional amount of viscosity change the flow condition, resulting in a 14% reduction in CTP.•Hole inclination above 60 degrees with mud −2 has a positive effect on CTP and improved up to 45%.•Velocity was found to have a significant impact on CTP as it could attain a maximum percentage of 96%. Globally, fuel energy has become a crucial issue in fulfilling energy demand; new oil/gas wells should be drilled safely and efficiently to achieve the well target. Cutting transport in deviated wells is directly affected by influencing parameters such as viscosity, annulus velocity of drilling mud, and hole inclination. As cuttings transport significantly affects drilling costs, time, and oil/gas well integrity. Poor hole cleaning efficiency could cause many drilling issues, including excessive torque and drag, Pipe washout and jamming, bit balling and washout, etc. Therefore, hole cleaning investigation requires a deep understanding of all influential parameters. The results of this study were utilized to investigate cutting transport performance, employing three different kinds of drilling mud. The investigational work was performed by a 10-feet elongated invisible pipe of 5-inch diameter and a steel pipe of 2-inch diameter as the test section. The cutting transport performance (CTP) was computed based on weight data for every single test. At different flow regimes, viscosity was examined in addition to two other influential parameters, namely fluid velocity and hole inclination. At all angles, during turbulent flow, Cutting Transport performance has enhanced up to 10% by increasing viscosity while keeping velocity constant. Nevertheless, an increasing additional amount of viscosity will turn the flow condition from turbulent to transient or laminar flow, resulting in a 14% reduction in CTP. It also shows that increasing hole angle above 60 degrees with mud-2 positively affects cuttings transport performance. It will be improved up to 45%. Moreover, a maximum of 96 percent CTP can be attained by drilling fluid velocity. Therefore, this study properly investigates the influence of viscosity, velocity, and hole inclination on cutting transporter performance, as a result saving drilling time and reducing hidden costs, as well as lead to a prediction of the carrying capacity of fluids and facilitating the optimum design of vertical and directional wells. Moreover, this study provides a guideline to analyze and enable the adjustment of drilling parameters to optimize the overall drilling process. [Display omitted]